(untitled) (Research, Society and Development, 2026)
Asthma is a chronic inflammatory disease of the airways with high prevalence and substantial clinical impact in adults, particularly when disease control is inadequate. Sleep disorders are among the factors associated with poor control and remain frequently under-recognized in clinical practice. This study aimed to analyze the association between asthma and sleep disorders in adults, with emphasis on clinical implications. A qualitative narrative review was conducted based on searches in PubMed and the Regional Portal of the Virtual Health Library (BVS), including full-text studies in English or Portuguese published in the last five years. After screening, eligibility assessment and removal of duplicates, 35 studies were included. The evidence shows a consistent association between asthma and sleep disorders, especially obstructive sleep apnea and insomnia, which are linked to worse asthma control, more frequent exacerbations, intensified nocturnal symptoms and impaired quality of life. Additional findings support a potentially bidirectional interaction between sleep disturbances and asthma and highlight the contribution of circadian mechanisms to nocturnal worsening. In conclusion, sleep disorders are relevant comorbidities in adults with asthma and should be systematically considered in clinical management to optimize control and health outcomes.